2022
DOI: 10.3390/ijms231810624
|View full text |Cite
|
Sign up to set email alerts
|

New Atypical Antipsychotics in the Treatment of Schizophrenia and Depression

Abstract: Schizophrenia and depression are heterogeneous disorders. The complex pathomechanism of the diseases imply that medication responses vary across patients. Many psychotropic drugs are available but achieving optimal therapeutic effect can be challenging. The evidence correlates well with clinical observations, suggesting that new atypical antipsychotic drugs are effective against negative and cognitive symptoms of schizophrenia, as well as against affective symptoms observed in depression. The purpose of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…However, radioligand binding studies have shown no affinity of JJGW07 for 5-HT 6 receptors, suggesting that other biological targets are involved in its pharmacological effects. Importantly, the memory-enhancing activity is not only dependent on the modulation of 5-HT 6 receptors, as there are other antipsychotics, i.e., aripiprazole, brexpiprazole, or cariprazine, that show procognitive properties due to other mechanisms, including interactions with the 5-HT 1A and/or 5-HT 7 receptors [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, radioligand binding studies have shown no affinity of JJGW07 for 5-HT 6 receptors, suggesting that other biological targets are involved in its pharmacological effects. Importantly, the memory-enhancing activity is not only dependent on the modulation of 5-HT 6 receptors, as there are other antipsychotics, i.e., aripiprazole, brexpiprazole, or cariprazine, that show procognitive properties due to other mechanisms, including interactions with the 5-HT 1A and/or 5-HT 7 receptors [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the role 5-HT 2A R antagonism plays in rescuing negative symptoms and cognitive deficits may be less critical . While some atypical antipsychotics with 5-HT 2A R antagonism/inverse agonism have shown adjunct therapeutic benefits for depression, , these drugs are polypharmacological compounds, making it difficult to interpret the specific role of 5-HT 2A R antagonism in their overall therapeutic effects. Recent evidence from clinical trials with psychedelics has shown that the activation of 5-HT 2A R holds promise for the discovery of novel antidepressants.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Against this background, a number of studies of clinical practice in antipsychotics prescription in children and adolescents have been reported from many countries -primarily Europe [6][7][8][9][10][11], with a few from other countries also, including Japan [12][13][14][15]. Of note, however, all these previous studies evaluated the period prior to 2018, and may not have fully covered the new antipsychotics released onto the market in recent decades, including brexpiprazole and lurasidone hydrochloride [16][17][18]. Additionally, stress and similar effects arising from the coronavirus pandemic are reported to have affected the prevalence of mental illness and antipsychotic treatment [19][20][21].…”
Section: Introductionmentioning
confidence: 99%